2022
DOI: 10.1186/s12885-022-09315-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system lymphoma high incidence and poor survival in Finnish population-based analysis

Abstract: Background We report here the first population-based incidence rates and prognosis of primary central nervous system lymphoma (PCNSL) in Finland. Methods Finnish Cancer Registry data by histological diagnosis and tumor location (2007–2017) for cases with diffuse large B-cell lymphoma. Results During 2007–2017, 392 new cases of PCNSL were reported (195 males, 197 females). The average age-adjusted incid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This study is limited by its retrospective design and the restricted number of patients that could be included, especially in comparison with other biomarker studies. Thus, our results should be confirmed in a larger and ethnically more diverse patient cohort; nevertheless, there was sufficient post‐hoc power of 0.902 and 70 patients is a considerable number, given that CNSL is a rare disease with an incidence number ranging from 0.17 to 0.63/100000 person‐years in epidemiological studies from different continents (Eloranta et al., 2018; Farrall & Smith, 2021; Ostrom et al., 2022; Puhakka et al., 2022; Shin et al., 2015). Also, the comparatively high number of SCNSL in the lymphoma group might reduce the validity of the results for PCNSL patients.…”
Section: Discussionmentioning
confidence: 96%
“…This study is limited by its retrospective design and the restricted number of patients that could be included, especially in comparison with other biomarker studies. Thus, our results should be confirmed in a larger and ethnically more diverse patient cohort; nevertheless, there was sufficient post‐hoc power of 0.902 and 70 patients is a considerable number, given that CNSL is a rare disease with an incidence number ranging from 0.17 to 0.63/100000 person‐years in epidemiological studies from different continents (Eloranta et al., 2018; Farrall & Smith, 2021; Ostrom et al., 2022; Puhakka et al., 2022; Shin et al., 2015). Also, the comparatively high number of SCNSL in the lymphoma group might reduce the validity of the results for PCNSL patients.…”
Section: Discussionmentioning
confidence: 96%
“…971–977). A study reported that the 2-year age-adjusted relative survival rate of PCNSL was 33%, and the corresponding 5-year survival rate of PCNSL was 26% [ 6 ]. An accurate diagnosis is crucial for the effective treatment of PCNSL.…”
Section: Instructionmentioning
confidence: 99%
“…1 It rises with age to reach 2.0/100,000 at age 60 and above, 2 and ascends to 2.93/100,000 among patients aged 75-79 years. 3 Elderly patients, aged 60 and above, comprise up to 65% of all PCNSL patients. 4 The treatment of PCNSL is challenging as the presence of the blood-brain barrier limits the scope of therapeutic agents that can penetrate the brain and attain therapeutic drug concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of PCNSL is 0.4 per 100,000 person‐years 1 . It rises with age to reach 2.0/100,000 at age 60 and above, 2 and ascends to 2.93/100,000 among patients aged 75–79 years 3 . Elderly patients, aged 60 and above, comprise up to 65% of all PCNSL patients 4 …”
Section: Introductionmentioning
confidence: 99%